Failure of human rhombic lip differentiation underlies medulloblastoma formation - Hendrikse, Liam D; Haldipur, Parthiv; Saulnier, Olivier; Millman, Jake; Sjoboen, Alexandria H; Erickson, Anders W; Ong, Winnie; Gordon, Victor; Coudière-Morrison, Ludivine; Mercier, Audrey L; Shokouhian, Mohammad; Suárez, Raúl A; et al. (Nature, 2022)
Medulloblastoma (MB) comprises a group of heterogeneous paediatric embryonal neoplasms of the hindbrain with strong links to early development of the hindbrain1-4. Mutations that activate Sonic hedgehog signalling lead to Sonic hedgehog MB in the upper rhombic lip (RL) granule cell lineage5-8. By contrast, mutations that activate WNT signalling lead to WNT MB in the lower RL9,10. However, little is known about the more commonly occurring group 4 (G4) MB, which is thought to arise in the unipolar brush cell lineage3,4. Here we demonstrate that somatic mutations that cause G4 MB converge on the core binding factor alpha (CBFA) complex and mutually exclusive alterations that affect CBFA2T2, CBFA2T3, PRDM6, UTX and OTX2. CBFA2T2 is expressed early in the progenitor cells of the cerebellar RL subventricular zone in Homo sapiens, and G4 MB transcriptionally resembles these progenitors but are stalled in developmental time. Knockdown of OTX2 in model systems relieves this differentiation blockade, which allows MB cells to spontaneously proceed along normal developmental differentiation trajectories. The specific nature of the split human RL, which is destined to generate most of the neurons in the human brain, and its high level of susceptible EOMES+KI67+ unipolar brush cell progenitor cells probably predisposes our species to the development of G4 MB.
Keywords: mutace; Muscle Proteins; antigen Ki-67; Cell Lineage; Repressor Proteins; svalové proteiny; buněčný rodokmen; transkripční faktory; represorové proteiny; mozeček; Hedgehog Proteins; buněčná diferenciace; transkripční faktory PEBP2A; lidé; Otx Transcription Factors; nádory mozečku; Medulloblastoma; Transcription Factors; Mutation; Core Binding Factor alpha Subunits; proteiny T-boxu; Cerebellar Neoplasms; metencephalon; Metencephalon; histondemethylasy; T-Box Domain Proteins; meduloblastom; Cerebellum; Ki-67 Antigen; Histone Demethylases; Cell Differentiation; proteiny hedgehog; transkripční faktory Otx; Humans